The incidence and clinical characteristics of herpes zoster among children and adolescents after implementation of varicella vaccination - Civen, Rachel; Chaves, Sandra S; Jumaan, Aisha; Wu, Han; Mascola, Laurene; Gargiullo, Paul; Seward, Jane F (The Pediatric infectious disease journal, 2009)
The varicella-zoster virus (VZV) vaccine strain may reactivate to cause herpes zoster. Limited data suggest that the risk of herpes zoster in vaccinated children could be lower than in children with naturally acquired varicella. We examine incidence trends, risk and epidemiologic and clinical features of herpes zoster disease among children and adolescents by vaccination status. Population-based active surveillance was conducted among <20 years old residents in Antelope Valley, California, from 2000 through 2006. Structured telephone interviews collected demographic, varicella vaccination and disease histories, and clinical information. From 2000 to 2006, the incidence of herpes zoster among children<10 years of age declined by 55%, from 42 cases reported in 2000 (74.8/100,000 persons; 95% confidence interval [95% CI]: 55.3-101.2) to 18 reported in 2006 (33.3/100,000; 95% CI: 20.9-52.8; P<0.001). During the same period, the incidence of herpes zoster among 10- to 19-year-olds increased by 63%, from 35 cases reported in 2000 (59.5/100,000 persons; 95% CI: 42.7-82.9) to 64 reported in 2006 (96.7/100,000; 95% CI: 75.7-123.6; P<0.02). Among children aged<10 years, those with a history of varicella vaccination had a 4 to 12 times lower risk for developing herpes zoster compared with children with history of varicella disease. Varicella vaccine substantially decreases the risk of herpes zoster among vaccinated children and its widespread use will likely reduce overall herpes zoster burden in the United States. The increase in herpes zoster incidence among 10- to 19-year-olds could not be confidently explained and needs to be confirmed from other data sources.